Impact of Interleukin 10 Deficiency on Intestinal Epithelium Responses to Inflammatory Signals - Papoutsopoulou, Stamatia; Pollock, Liam; Walker, Catherine; Tench, William; Samad, Sakim Shakh; Bergey, François; Lenzi, Luca; Sheibani-Tezerji, Raheleh; Rosenstiel, Phillip; Alam, Mohammad Tauqeer; Martins Dos Santos, Vitor A. P.; Müller, Werner; et al. (Frontiers in Immunology, 2021)
Interleukin 10 (IL-10) is a pleiotropic, anti-inflammatory cytokine that has a major protective role in the intestine. Although its production by cells of the innate and adaptive immune system have been extensively studied, its intrinsic role in intestinal epithelial cells is poorly understood. In this study, we utilised both ATAC sequencing and RNA sequencing to define the transcriptional response of murine enteroids to tumour necrosis factor (TNF). We identified that the key early phase drivers of the transcriptional response within intestinal epithelium were NFkappaB transcription factor dependent. TNF-induced Il10-/- enteroids showed significant downregulation of identified NFkappaB target genes Tnf and Ccl20, and delayed overexpression of NFkappaB inhibitor encoding genes, Nfkbia and Tnfaip3. Similar responses were observed in vivo. IL-10 deficiency, or immunoblockade of IL-10 receptor, impacted on TNF-induced endogenous NFkappaB activity in enteroids. Intestinal epithelium-derived IL-10 appears to play a crucial role as a positive regulator of the canonical NFkappaB pathway, contributing to maintenance of intestinal homeostasis. This is particularly important in the context of an inflammatory environment and highlights the potential for future tissue-targeted IL-10 therapeutic intervention.